Draba ancashensis (Brassicaceae; Cruciferae), a new species from Peru and a key to the Peruvian species of the genus - Al-Shehbaz, Ihsan A.; Cano, Asunción; Trinidad, Huber (Phytotaxa, 2019)
Draba ancashensis is described, illustrated, and its relationship to the other species of the genus, especially the Peruvian, is discussed. A key to the 26 (17 endemic) native Peruvian species of Draba is provided to facilitate the easy determination of species. Status of two annual species of Draba is evaluated. Distribution of the species at the department level is also given.